Quantitative Assessment of the Evolution of Indonesia International Military Cooperation with the United States and China (1995 – 2014) - Rasyid, Muhammad Gilang; Nashir, Asep Kamaluddin; Saripudin, Mohamad Hery (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2026)
The dynamics of China and the United States rivalry have significantly affected many countries, with both seeking to align other states with them. Both the United States and China seek to increase their influence amid geopolitical competition, including military cooperation with Indonesia. Following the question of how these two relationships have developed over time, we present a quantitative analysis of the evolution, trend, and variations of international military cooperation with both China and the United States. With that in mind, this study developed an original index, the International Military Cooperation Intensity (IMCI) Index, aimed at measuring military cooperation between Indonesia and the two countries from 1995 to 2014 within arms transfer and bilateral joint military exercises area. The findings from the IMCI Index show that while Indonesia has increasingly strengthened its military cooperation with the United States, it has simultaneously strengthened its relationship with China. While our findings verify the assumption that United States remains Indonesia’s stronger partner, the results confirm Indonesia’s  increasing military cooperation with China during this period. This result increases our understanding of Indonesia's evolving military cooperation with both countries during this period using these two quantitative indicators. In addition, the methodological approach used in this study illustrated the usefulness of constructing an index that can serve to show the trends, evolution, and variation in examining international relations events such as international military cooperation.